ADMINISTRATIVE-COMMAND METHODS AND THEIR INFLUENCE ON THE SOCIETY OF KARAKALPAKSTAN IN 1937-1941 (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The work analyzes the internal politics and social processes in the Karakalpak ASSR in 1937-1941. Particular attention is paid to repression, collectivization, and administrative methods of governance. The influence of authoritarian modernization on the social life of the region is emphasized.